1995
DOI: 10.1007/bf01720972
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of mental states and biofeedback techniques: Effects on breathing pattern

Abstract: The purpose of the present study was to examine whether breathing pattern may be used as a reliable index for the effectiveness of techniques applied for the regulation of mental states. Heart rate (HR), breathing pattern, galvanic skin response (GSR), and electromyogram (EMG) of the frontalis muscle were measured in 39 male and female subjects aged 18-25 years during 10-minute treatment with relaxation technique (autogenic training and/or music) followed by 10 minutes of imagery training. In the first 7 sessi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 29 publications
3
13
1
Order By: Relevance
“…The extent of this increase depended on the difficulty of the cognitive task (Mehler et al 2009). In contrast, relaxation is associated with a decrease in respiratory frequency (Blumenstein et al 1995). In our study, we observed the largest increase in respiratory frequency (i.e., decrease in T tot ) in conditions P1, N1 and S, which were the conditions with the highest attentional demand.…”
Section: Effects On Breathing Patterncontrasting
confidence: 61%
“…The extent of this increase depended on the difficulty of the cognitive task (Mehler et al 2009). In contrast, relaxation is associated with a decrease in respiratory frequency (Blumenstein et al 1995). In our study, we observed the largest increase in respiratory frequency (i.e., decrease in T tot ) in conditions P1, N1 and S, which were the conditions with the highest attentional demand.…”
Section: Effects On Breathing Patterncontrasting
confidence: 61%
“…Although these findings emphasize the consistency of our results, using larger numbers of well-described cases should control them further. It is noteworthy that heart rates are connected to breathing patterns, which have in turn been considered to be a sensitive psychophysiological index for sportsmen (Blumenstein et al, 1995). These results could be associated with the reduction of pain achieved for patients of class Q5, consistent with previously reported success in similar cases (Borgeat, Elie, & Larouche, 1985).…”
Section: Journal Of Neurotherapysupporting
confidence: 83%
“…Systolic and diastolic blood pressure as well as heart rate changes were monitored from the beginning to the end of each session (and therefore from beginning to end of the entire treatment) in order to examine whether physiological effects could be observed at the cardiovascular level. An influence of biofeedback on heart rate was recently reported, in connection with EMG and breathing patterns (Blumenstein, Breslav, Bar-Eli, Tenenbaum, & Weinstein, 1995). Although the treatment goal was not to directly influence pulse rate in 8 JOURNAL OF NEUROTHERAPY the Blumenstein et al report or in our study, this parameter was recorded before and after each session.…”
Section: Patientsmentioning
confidence: 59%
“…Not surprisingly, what one is thinking about may affect the nature of the respiratory response. Activities that tend to be relaxing tend to decrease ventilation, and those that conjure images of activities may tend to increase ventilation (29). The variability of the respiratory pattern may be more susceptible to modification by mental activity than either the average level of ventilation or any specific aspect of the respiratory pattern (169).…”
Section: Cognitive and Emotional Activities That Interact With Breathingmentioning
confidence: 99%